Report on mission of Caribbean producers of ornamental flowers, foliage and pot plants to USA, Canada, Netherlands and West Germany - Natarajan, R. (CDB WildeyBB, 1985)
Reviews market condition in countries visited as expressed by the importers, wholesalers and distributors whom the Mission met. Reports results of discussions each Caribbean producer had with overseas importers and growers on varieties they were interested in obtaining and terms and conditions for supplying same, and on type of joint venture arrangement they were interested in. Contains price lists, plant importing procedures, information for foreign shippers and Canadian import regulations.